Quality of life and willingness to pay for receiving hemodialysis in patients who received peritoneal dialysis in Thailand - Wanchana Singhan; Unchalee Permsuwan; Surachet Vongsanim; Yuttitham Suteeka; Siwaporn Deeprom (Faculty of Pharmacy, Mahidol University, 2022)
This cross-sectional study was conducted to evaluate quality of life (QoL), willingness to pay (WTP) for receiving hemodialysis (HD), and factors influencing QoL in patients who received peritoneal dialysis (PD) in Thailand. Data of PD patients visiting secondary or tertiary hospitals from December 2020 through June 2021 were collected. EuroQoL EQ-5D-5L questionnaire was used to evaluate QoL. After the patients completed the questionnaire, they were interviewed using the contingent valuation method to derive their WTP for switching to HD. Patients randomly picked up one payment card as an initial price for receiving HD, then bidding by 100 Thai Baht (THB) up and down to reach the maximum affordable WTP amount. Multiple linear regression was used to identify factors affecting QoL. A total of 102 patients were included in this study. The mean age was 58 years. EQ-5D utility score was 0.71±0.32. Five variables were the factors that affect QoL included serum albumin, hospitalization, age, urine output, and hemoglobin level. Average WTP was 233±293 THB (7.2±9.0 USD) per HD session. Quality of life among these study patients was slightly higher than reported in Thai patients with low hemoglobin level. Treatment anemia to reach hemoglobin target and preservation of residual urine output might improve QoL. The average WTP for switching to HD among PD patients was only one-sixth of general billing price for HD.